2016
DOI: 10.1097/nmc.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Care for Women with Gestational Diabetes

Abstract: Postpartum GDM care could be improved by educating providers on the current postpartum GDM standard of care and use of the 5 A's framework for health promotion; prompting providers to order appropriate screenings and document the 5 A's; coordinating follow-up glucose screening and behavioral management with the postpartum visit and subsequent family planning visits; notifying primary care providers and pediatricians of the GDM diagnosis to ensure continuity of care; and referring to allied healthcare providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…23 Therefore, as noted in Table 1, the results are from a final sample of nine articles (2014-2018) 16,[23][24][25][26][27][28][29][30] , representing nine unique studies that examined rates of, predictors of, and barriers to postpartum follow-up and screening among women diagnosed with GDM (n=6), HDP (n=1), or both (n=2). Among these, six were based on review of medical records; [24][25][26][27][28]30 one was based on review of insurance claims; 16 one was based on review of data from a large data warehouse; 29 and, one was based on in-person questionnaires and interviews with postpartum women. 23 The duration of the follow-up period ranged six weeks to three years across a total of 22,554 women (sample size range of 97 to 12,622; median, 373) with complicated pregnancies during 2003-2016.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…23 Therefore, as noted in Table 1, the results are from a final sample of nine articles (2014-2018) 16,[23][24][25][26][27][28][29][30] , representing nine unique studies that examined rates of, predictors of, and barriers to postpartum follow-up and screening among women diagnosed with GDM (n=6), HDP (n=1), or both (n=2). Among these, six were based on review of medical records; [24][25][26][27][28]30 one was based on review of insurance claims; 16 one was based on review of data from a large data warehouse; 29 and, one was based on in-person questionnaires and interviews with postpartum women. 23 The duration of the follow-up period ranged six weeks to three years across a total of 22,554 women (sample size range of 97 to 12,622; median, 373) with complicated pregnancies during 2003-2016.…”
Section: Resultsmentioning
confidence: 99%
“…23 The duration of the follow-up period ranged six weeks to three years across a total of 22,554 women (sample size range of 97 to 12,622; median, 373) with complicated pregnancies during 2003-2016. Combined, the studies include a racially and ethnically diverse population of childbearing women with minority representation ranging from 31% to 89%; notably, six studies 16,[25][26][27][28]30 had > 69% minority representation in the samples, reflective of the high-risk population of women who experience complications of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, pediatric providers, including nurses and physicians, reported that coordinating care for both infants and mothers eventually became a routine process, despite the program’s novelty and initial challenges. Although novel for HPV vaccination, other studies have discussed involving pediatricians to coordinate women’s postpartum care including for postpartum depression (Liberto 2012), nutrition and physical activity (Taveras et al 2011), breastfeeding (Geraghty, Riddle, & Shaikh 2008), family planning (Caskey et al 2016), and management of gestational diabetes (Ortiz et al 2016). Our study provides evidence that such programs can be accepted by providers and embedded into clinical practice.…”
Section: Discussionmentioning
confidence: 99%